242. A new approach for MRI 3D image quality control: Protocol set up for multicoil arrays. (December 2018) - Mascaro, L.; Duina, A.; Moretti, R.
Abstract : Purpose: The use of RF multicoil arrays for MR imaging has demonstrated several advantages, however when the number of coil elements increases, both signal and noise can become very inhomogeneous over the scanned volume, so standard 2D evaluations, as proposed by many protocols, are no longer representative of the whole volume and a new approach has to be considered. In this work we set up an automatic 3D quality evaluation particularly suited for head coils. Methods: Measurements were performed on a Siemens Skyra 3T system with a 20 channel TX head coil, scanning an homogeneous spherical phantom with a standard clinical 3D protocol. Reconstruction was performed both for single sub-coil (uncombined images) and for the final image volume, that is a combination of all the sub-coils signals. Processing was performed offline with a bespoke imagej plugin. Main processing steps for combined volume are the automatic centring of a spherical region of interest (ROI) covering 80% of the phantom image volume, and the calculation of Signal to Noise Ratio (SNR), Normalized Absolute Average Difference (NAAD) and 5-color level reconstructed image with the NEMA algorithms for 2D images that were extended to 3D[1] . For uncombined sub-coil images, SNR is calculated in a 2 cm diameter sphere ROI automatically centered on the maximum average signal region, as showed in Fig. 1, and uniformity is evaluated with a 11-color levels volume reconstruction. Results: Results for volumetric analysis are compared to the evaluation performed on 2D images from standard planes centered at the phantom isocenter. Results are very different particularly for uncombined analysis where the single coil is far from the evaluation slice, as reported for example inTable 1 for the SNR of coil n.2. In this case parameter variations due to malfunctioning are less sensitive with a 2D analysis. Conclusions: We set up an automatic protocol for 3D quality evaluation which is more representative of the whole coil specification volume and more sensitive to failures when a single coil analysis is performed.